Postal consent for upper gastrointestinal endoscopy. Issue 1 (1st January 2000) - Shepherd, H A; Bowman, D; Hancock, B; Anglin, J; Hewett, D
Abstract : BACKGROUND: Standards for good practice in clinical risk management issued by the Clinical Negligence Scheme for Trusts indicate that "appropriate information is provided to patients on the risks and benefits of proposed treatment, and of the alternatives available before a signature on a consent form is sought". AIMS: To investigate the practicability and patient acceptability of a postal information and consent booklet for patients undergoing outpatient gastroscopy. METHODS: Information about gastroscopy procedure, personalised appointment details, and a carbonised consent form were compiled into a single booklet. This was mailed to patients well in advance of their endoscopic procedure. Patient satisfaction for this new process was assessed by questionnaire. RESULTS: 275 patients received a patient information booklet. Of these, 150 (54.5%) returned the consent form by post when they confirmed their attendance; 141 (94%) had signed the form, and the other nine requested further information. Of the remaining 125 booklets sent out, 115 (92%) forms were brought back on the day of the investigation having been previously signed. The remaining 10 (8%) required further information before signing the form. An audit of 168 patients was used to test reaction to the booklet and the idea of filling in the form before coming to hospital; 155 patients (92.2%) reported the information given in the booklet to be "very useful", and all reported it to be "clear and understandable". CONCLUSION: A specifically designed patient information booklet with integral consent form is accepted by patients, and improves the level of understanding prior to the investigation being carried out.